Interactions between Local Communities and Cultural Heritage: From Expectations to Realities. The Case of Lithuania - Kulevičius, Salvijus (Acta humanitarica academiae Saulensis, 2026)
At the turn of the 20th and 21st centuries, the paradigm of cultural heritage changed significantly. At that time, the view also became established that it is important to involve communities (heritage custodians “from below”) in heritage conservation processes – not only to include them, but also to regard the communities themselves as an equal or even the most important factor and actor in heritage protection. In this context, the term “heritage communities” can be interpreted broadly and flexibly, depending on the specific country and case under consideration.The object of this research is officially established and registered local communities in Lithuania. This is probably the largest group of official communities in Lithuania. The research aims to find out the extent to which theories and assumptions about the importance of heritage for the sense of community, identity, and self-awareness of social groups in general are true, and to what extent heritage is specifically important for local communities, as well as whether they inherently possess the potential and willingness to function as heritage communities. The findings of the research question the importance of heritage for local communities and reveal a distinctive perception of its benefits, where engagement with heritage is primarily associated not with the preservation of heritage itself, but with its benefits for the community. Heritage is not a value in itself; it is important only insofar as it can contribute to meeting the fundamental needs of the community.
Keywords: heritage communities; heritage discourse; local communities of Lithuania